Weight status influences the effect of hyperglycemia at admission on clinical outcomes after endovascular thrombectomy - Tao Tang; Xu-Sheng Zhao; Zhong-Jun Chen; Tie-Ping Fan; Aline M. Thomas; Man-Hong Zhao; Di Li; Shen Li (Brain Circulation)
BACKGROUND: Insulin resistance is more prevalent in the overweight population, which can affect their glucose metabolism. This study explores whether weight status influences the relationship between admission hyperglycemia and outcomes after thrombectomy. METHODS: Four hundred and fifty-two patients with acute anterior circulation ischemic stroke undergoing thrombectomy were retrospectively analyzed. Hyperglycemia at admission was described as venous blood glucose ≥7.8 mmol/L and overweight as body mass index ≥24 kg/m2. The outcomes included the rates of functional independence (90-day modified Rankin Scale 0–2), symptomatic intracranial hemorrhage within 24 h after thrombectomy, and mortality at 90 days. RESULTS: Overall, hyperglycemia at admission decreased the likelihood of functional independence (adjusted odds ratio [OR] 0.50, 95% confidence interval [CI] 0.30–0.83, P = 0.008). Weight status modified the efficacy of admission hyperglycemia on functional independence (P = 0.022 for interaction). Hyperglycemia at admission was negatively associated with functional independence among overweight patients (adjusted OR 0.30, 95% CI 0.15–0.60, P = 0.001) but not among normal-weight patients (adjusted OR 1.13, 95% CI 0.48–2.70, P = 0.776). Weight status did not influence the efficacy of hyperglycemia at admission on mortality (P = 0.201 for interaction) or symptomatic intracerebral hemorrhage (P = 0.105 for interaction). CONCLUSIONS: Weight status influenced the effect of hyperglycemia at admission on functional independence after thrombectomy. Hyperglycemia at admission was related to functional independence among overweight patients but not among normal-weight patients. Our findings suggest tight control of glucose may be needed for overweight patients in the thrombectomy setting.